Can perception be extended to a "feel of north"? Tests of automaticity with the NaviEar. (June 2023) - Witzel, Christoph; Lübbert, Annika; O'Regan, J. Kevin; Hanneton, Sylvain; Schumann, Frank
This study investigated the potential for the development of novel perceptual experiences through sustained training with a sensory augmentation device. We developed (1) a new geomagnetic sensory augmentation device, the NaviEar, and (2) a battery of tests for automaticity in the use of the device. The NaviEar translates head direction toward north into continuous sound according to a "wind coding" principle. To facilitate automatization of use, its design is informed by considerations of the embodiment of spatial orientation and multi-sensory integration, and it uses a sensory coding scheme derived from means for auditory perception of wind direction that is common in sailing because it is easy to understand and use. The test battery assesses different effects of automaticity (interference, rigidity of responses, and dynamic integration) assuming that automaticity is a necessary criterion to show the emergence of perceptual feel, that is, an augmented experience with perceptual phenomenal quality. We measured performance in simple training tasks, administered the tests for automaticity, and assessed subjective reports through a questionnaire. Results suggest that the NaviEar is easy and comfortable to use and has a potential for applications in real-world situations. Despite high usability, however, a 5-day training with the NaviEar did not reach levels of automaticity that are indicative of perceptual feel. We propose that the test battery for automaticity may be used as a benchmark test for iterative research on perceptual experiences in sensory augmentation and sensory substitution.